Malnutrition and Disability: Evaluating Factors Influencing Severe Malnutrition In Children With Cerebral Palsy In Lusaka, Zambia - Micah Mutuna Simpamba (The Center for Disability Studies and Services Brawijaya University, 2020)
The aim of this study was to identify the main risk factors associated with severe malnutrition in children with CP. An unmatched case control study was used to compare 33 children with CP presenting with severe malnutrition (WAZ â‰¤ -3 SD) against 66 non malnourished CP children (WAZ â‰¥ -2SD) at the University Teaching Hospital in Lusaka. Risk factors for severe malnutrition in children with CP were determined with bivariate and multiple logistic regression. A p-value of < 0.05 was considered significant at 95% confidence interval. After adjusting for other variables, factors that remained statistically significant (p-value < 0.05) included the following: use of Â unflushed pit latrine toilet (p=0.0119); bilateral CP (p=0.0054); GMFCS level 4 or 5 (p=0.0001); history of illness in the past six months (p=0.0241); swallowing difficulties (p=0.0006); tonic bite (p= 0.0011no weight gain in the past 2 to 3 months (p=0.0001); dependent on feeding (p=0.0061); feeds only on semisolids or liquids (p=0.0231); taking more than 30 minutes feeding (p=0.0381); fed for â‰¤ 3 times/day (0.0025); child opening bowels after 3 or more days (0.0057); caregiver concerned about child's feeding difficulties (p=0.0076); not likely to be fed Irish potatoes (p=0.0008) and Fish (p=0.0001). The risk factors identified in the current study are related to the child's severity and feeding difficulties including caregiver caring practices.